2021
DOI: 10.1111/jch.14386
|View full text |Cite
|
Sign up to set email alerts
|

Baseline prevalence of high blood pressure and its predictors in a rural adult population of Bangladesh: Outcome from the application of WHO PEN interventions

Abstract: This cross‐sectional study estimated the prevalence of high blood pressure (BP) and examined its predictors at baseline following protocol 1 (actions 1 and 2) of World Health Organization (WHO) Package of Essential Noncommunicable Disease (PEN) Interventions in a selected rural area of Bangladesh. A total of 11 145 adults (both sex and age ≥ 18 years) completed both the questionnaire and clinical measurements at the household and community clinics, respectively. We defined high BP as systolic BP ≥ 120 mmHg or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 62 publications
1
8
0
Order By: Relevance
“…However, according to the most recent STEPwise approach to surveillance (STEPS) survey conducted in Bangladesh (2018) data [ 38 ], the prevalence of hypertension was 25.2% among the urban slum dwellers which is close to what is reported among the slum dwellers in this study. A recent study conducted in rural Bangladesh also reported a similar (25.9%) prevalence of hypertension among the adult population [ 39 ]. The prevalence of hypertension was higher than those reported in slums from Brazil (21%) [ 22 ] and Kenya (12.3%) [ 23 ], but lower than those from Nigeria (38.2%) [ 21 ] and Kolkata (42%) [ 20 ].…”
Section: Discussionmentioning
confidence: 69%
“…However, according to the most recent STEPwise approach to surveillance (STEPS) survey conducted in Bangladesh (2018) data [ 38 ], the prevalence of hypertension was 25.2% among the urban slum dwellers which is close to what is reported among the slum dwellers in this study. A recent study conducted in rural Bangladesh also reported a similar (25.9%) prevalence of hypertension among the adult population [ 39 ]. The prevalence of hypertension was higher than those reported in slums from Brazil (21%) [ 22 ] and Kenya (12.3%) [ 23 ], but lower than those from Nigeria (38.2%) [ 21 ] and Kolkata (42%) [ 20 ].…”
Section: Discussionmentioning
confidence: 69%
“…There are about 35 704 adults (≥18 years old) in the Dhangora union. Further details of the study design, setting and participant is published in articles on malnutrition and hypertension from the same parent study 30 31…”
Section: Methodsmentioning
confidence: 99%
“…The online platform allowed linking data collected at the CC with those collected at the household level. The data collection instrument and procedure is also described in our earlier publication 31…”
Section: Methodsmentioning
confidence: 99%
“…All physical measurements were carried out maintaining adequate privacy. The details of the study methods are elaborately described elsewhere 23 , 24 .…”
Section: Methodsmentioning
confidence: 99%